Exploring Jesus' High Priestly Identity - Adeoye, Moses Adeleke (Department of Comparative Study of Religions, 2025)
This article explores Jesus' high priestly identity within Christian theology, focusing on its significance in the Old Testament priesthood. The role of the high priest was central to the religious and cultural life of the ancient Jewish community, serving as an intermediary between God and the people. The theological and historical controversy about Jesus' position as high priest is one of the main issues discussed. The paper examines theological, historical and biblical data to explore this issue thoroughly. The research question is: What are the theological implications of Jesus' identity as the High Priest? The research method involves biblical exegesis, historical analysis, and theological reflection. The study clarifies the complex relationship between the role of Jesus and the conventional information about the high priest using the Old Testament image of the high priest and the Jewish religious framework and the New Testament depiction of Jesus in the context of the priesthood. The study also considers how Christian theology, which understands redemption, reconciliation, and mediation, might be affected by Jesus' eventual elevation to the rank of high priest. The research results reveal the profound implications of Jesus' identity as the High Priest regarding its continuity with the Old Testament priesthood and its transformative impact on the Christian understanding of salvation and redemption. In conclusion, this exploration of Jesus' high priestly identity promises to enrich our understanding of the depth and significance of Christ's redemptive work.